If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + -2x = -1(-1 + -3x) + -8 18 + -2x = (-1 * -1 + -3x * -1) + -8 18 + -2x = (1 + 3x) + -8 Reorder the terms: 18 + -2x = 1 + -8 + 3x Combine like terms: 1 + -8 = -7 18 + -2x = -7 + 3x Solving 18 + -2x = -7 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 18 + -2x + -3x = -7 + 3x + -3x Combine like terms: -2x + -3x = -5x 18 + -5x = -7 + 3x + -3x Combine like terms: 3x + -3x = 0 18 + -5x = -7 + 0 18 + -5x = -7 Add '-18' to each side of the equation. 18 + -18 + -5x = -7 + -18 Combine like terms: 18 + -18 = 0 0 + -5x = -7 + -18 -5x = -7 + -18 Combine like terms: -7 + -18 = -25 -5x = -25 Divide each side by '-5'. x = 5 Simplifying x = 5
| 22.8-2p=444 | | 6(h+4)=-2l | | 9w+14w+18=-8(-9w+20)-18 | | -(4n+6)+8=-6(n+1)2n | | (n+3)(8n+1)=0 | | 7.5x^2-6x-9.8=0 | | -3j=7(-4j+20)+18j | | R-9=-5 | | -4(-7z+16)=7(3z+15)+20z | | -(9-3x)=11 | | 0.20(y-6)+0.06y=0.18y-0.03(30) | | -4-6k+6-8=-6-6k | | (2x)+3=(4x)-3 | | 8(4k+1)=15k+6(10k-13) | | 6t^2-26t+22=0 | | 0.75x+5y=20 | | 8x-3x^2+2x= | | 12x+20=-40 | | (-1x)+2=2+(-4x) | | -4s=-5(s-5) | | 4x^2+160=0 | | 24+x=54 | | (fg)(x)=(5x-2)(3x^2) | | 38+5x=-32 | | 6(x-4)+3x=5(2x+8)-14 | | 9x+7=7x+37 | | 12+4q+1=5(q+5) | | c+1-3=-21 | | .05t+.012(t+1)=.57 | | -4(17y-15)=-6(4+12y) | | 2(1.43)-y=7 | | G(5n)=2x^2-5 |